Robin Hood : prince of thieves [videorecording (DVD)] - Kamen, Michael (Warner Bros. Entertainment., 2010)
After returning home from the crusades and finding his home gone and the people of Sherwood oppressed by the evil Sheriff of Nottingham, Robin fights for the good of all men and the love of one woman.